Risk of benign paroxysmal positional vertigo in patients with depressive disorders: a nationwide population-based cohort study. Issue 3 (30th March 2019) - Hsu, Chiao-Lin; Tsai, Shih-Jen; Shen, Cheng-Che; Lu, Ti; Hung, Yao-Min; Hu, Li-Yu
Abstract : Objective: The association between depression and benign paroxysmal positional vertigo (BPPV) remains debated. This study aimed to investigate the risk of BPPV in patients with depressive disorders. Design: Longitudinal nationwide cohort study. Setting: National health insurance research database in Taiwan. Participants: We enrolled 10 297 patients diagnosed with depressive disorders between 2000 and 2009 and compared them to 41 188 selected control patients who had never been diagnosed with depressive disorders (at a 1:4 ratio matched by age, sex and index date) in relation to the risk of developing BPPV. Methods: The follow-up period was defined as the time from the initial diagnosis of depressive disorders to the date of BPPV, censoring or 31 December 2009. Cox proportional hazard regression analysis was used to investigate the risk of BPPV by sex, age and comorbidities, with HRs and 95% CIs. Results: During the 9-year follow-up period, 44 (0.59 per 1000 person-years) patients with depressive disorders and 99 (0.33 per 1000 person-years) control patients were diagnosed with BPPV. The incidence rate ratio of BPPV among both cohorts calculating from events of BPPV per 1000 person-years of observation time was 1.79 (95% CI 1.23 to 2.58, p=0.002). Following adjustments for age, sex and comorbidities, patients with depressive disorders were 1.55 times more likely to develop BPPV (95% CI 1.08 to 2.23, p=0.019) as compared with control patients. In addition, hyperthyroidism (HR=3.75, 95% CI 1.67–8.42, p=0.001) and systemic lupus erythematosus (SLE) (HR=3.47, 95% CI 1.07 to 11.22, p=0.038) were potential risk factors for developing BPPV in patients with depressive disorders. Conclusions: Patients with depressive disorders may have an increased risk of developing BPPV, especially those who have hyperthyroidism and SLE.